The Cooperative Learning Comparison of Student Teams Achievement Division Type and Teams Assisted Individualization type Toward The Students’ Mathematical Communication Skill - Mutmainnah Tahir; Thamrin Tayeb; Muh. Rusydi Rasyid; Fitriani Nur; munawarah munawarah (Universitas Negeri Makassar, 2020)
Abstract:The study aimed to compare the cooperative learning model of Student Team Achievement Division (STAD) and Team Assisted individualization (TAI) types on the mathematical communication skill of class VIII students of State Junior High School 3 Sungguminasa of Gowa Regency. It was quasi-experimental research with non-equivalent control group design. The study population was all the students of class VIII of State Junior High School 3 Sungguminasa. Descriptive and inferential statistical analysis with independent sample t-test were used in analysing the data. Based on the results of the descriptive statistical analysis, the mean score of the students' mathematical communication skill using cooperative learning model of STAD type was about 65.63% at the high category and the rest score was at the very high category; while the mean score of the students’ mathematical communication skill using the cooperative learning model of TAI type was about 62.5% at the high category and the rest score was at very high category. Based on the inferential analysis, it was obtained the results that there were the differences of the mean scores of the students’ mathematical communication skill who possessed the STAD and TAI learning types, and TAI learning type was more effective than the STAD learning type to enhance the students' mathematical communication skill.